2000
DOI: 10.1128/jb.182.13.3767-3774.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the furA and catC Operon, Encoding a Ferric Uptake Regulator Homologue and Catalase-Peroxidase, Respectively, in Streptomyces coelicolor A3(2)

Abstract: We isolated the catC gene, encoding catalase-peroxidase in Streptomyces coelicolor, using sequence homology with the katG gene from Escherichia coli. Upstream of the catC gene, an open reading frame (furA) encoding a homologue of ferric uptake regulator (Fur) was identified. S1 mapping analysis indicated that the furA gene was cotranscribed with the catC gene. The transcriptional start site of the furA-catC mRNA was mapped to the translation start codon ATG of the furA gene. The putative promoter contains cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 40 publications
1
42
1
Order By: Relevance
“…1A). A similar linkage of the furA and katG orthologs is also seen in Streptomyces coelicolor (furA-catC) and Streptomyces reticuli (furS-cpeB) (18,50). S. coelicolor furA is highly homologous to the furA gene from M. tuberculosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1A). A similar linkage of the furA and katG orthologs is also seen in Streptomyces coelicolor (furA-catC) and Streptomyces reticuli (furS-cpeB) (18,50). S. coelicolor furA is highly homologous to the furA gene from M. tuberculosis.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, recent studies including inactivation of mycobacterial furA have demonstrated that it is a negative regulator of katG (47). A similar role for FurA has also been reported for S. coelicolor (18), albeit based on indirect observations without inactivating the furA gene in this organism. Interestingly, the S. coelicolor FurA is closely related to FurA of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
“…Expression of katG is derepressed in a furA mutant, consistent with a role for FurA as a repressor of catalaseperoxidase expression (Pym et al, 2001). In S. coelicolor, the catC catalase-peroxidase is co-transcribed with furA, which serves as a metal-sensing repressor for the furA-catC operon, but this operon does not appear to be inducible by H 2 O 2 (Hahn et al, 2000b). Finally, in Desulfovibrio vulgaris, a peroxide stress operon encodes a fur homologue together with rubrerythin, which functions in oxidative stress resistance (Lumppio et al, 1997;.…”
Section: The Perr Familymentioning
confidence: 76%
“…However, Escolar et al (1999) observed that a minimum of three repeats of the hexamer, N-AT A /TAT, regardless of orientation, was required for effective Fur binding. Additional studies using gel retardation assays and DNA footprinting would provide valuable information on potential Fur-regulated promoters (Frechon and Cam, 1994 Bagg and Neilands, 1987;deLorenzo et al, 1987;Gonzalez et al, 1999, Hahn et al, 2000vanVliet et al, 1999). Recently, Althaus et al (1999) …”
Section: Discussionmentioning
confidence: 99%
“…The tightly associated Zn ion is coordinated with two sulfur ligands, Cys92 and Cys95, and two nitrogen or oxygen ligands (Jacquamet et al, 1998). The two cysteine residues are known to be essential for DNA-binding activity (Coy et al, 1994) and are conserved in most Fur-homologous proteins (Hahn et al, 2000). However, only genomic sequence data are available on the fur homolog in B. burgdorferi (Fraser et al, 1997).…”
Section: Identified E Colimentioning
confidence: 99%